SOSIALISASI PENGHENTIAN SUNAT PADA ANAK PEREMPUAN DAN PEREMPUAN PADA KELOMPOK IBU DHARMA WANITA KLHK PROVINSI KALIMANTAN TIMUR - Tri Wahyuni; dwi rahmah Fitriani; Faried Rahman Hidayat; Meliana Susanti (Open Edutech Indonesia, 2023)
Female Genital Cutting and Mutilation (FGCM) or female circumcision is an old practice that is still widely practiced in various parts of the world, including Indonesia. The implementation of female circumcision is linked to religious and cultural values, so it gives the impression of being a medicalization that parents must carry out for their daughters because they are worried that they will be ostracized or deemed not to comply with religious law. The aim of this community service is socialization to jointly stop the behavior of circumcising girls in the neighborhood where Darma Wanita lives. Community service utilizes counseling at the Dharma Wanita UPT Ministry of Environment and Forestry. The results of this activity increased the knowledge of mothers of Dharma Wanita members regarding the prohibition of female circumcision both from a health and religious perspective, as well as understanding the side effects of female circumcision for children who experience it. Apart from that, there was a commitment raised by the majority of participants in outreach activities not to allow their children, grandchildren, or relatives to undergo female circumcision.